2016
DOI: 10.1021/acs.jmedchem.5b01857
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design and Synthesis of 3-Amino-1,5-dihydro-4H-pyrazolopyridin-4-one Derivatives as Tyrosine Kinase 2 Inhibitors

Abstract: We report herein the discovery and optimization of 3-amino-1,5-dihydro-4H-pyrazolopyridin-4-one TYK2 inhibitors. High-throughput screening against TYK2 and JAK1-3 provided aminoindazole derivative 1 as a hit compound. Scaffold hopping of the aminoindazole core led to the discovery of 3-amino-1,5-dihydro-4H-pyrazolopyridin-4-one derivative 3 as a novel chemotype of TYK2 inhibitors. Interestingly, initial SAR study suggested that this scaffold could have a vertically flipped binding mode, which prompted us to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…To avoid significant hydrolysis of the ester functionality, it was important to run the reaction at a relatively low temperature (75 °C) and within a relatively short period of time (4 h). In the same manner, 41b was obtained from 40, which was prepared from 3-bromo-5-fluoro-2methoxyaniline (39). Treatment of 41a and 41b with 4,6dichloro-N-(methyl-d 3 )pyridazine-3-carboxamide (37) 53 in the presence of lithium bis(trimethylsilyl)amide resulted in chloropyridazine carboxamides 42a and 42b, which were then converted to 43a and 43b by Buchwald reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid significant hydrolysis of the ester functionality, it was important to run the reaction at a relatively low temperature (75 °C) and within a relatively short period of time (4 h). In the same manner, 41b was obtained from 40, which was prepared from 3-bromo-5-fluoro-2methoxyaniline (39). Treatment of 41a and 41b with 4,6dichloro-N-(methyl-d 3 )pyridazine-3-carboxamide (37) 53 in the presence of lithium bis(trimethylsilyl)amide resulted in chloropyridazine carboxamides 42a and 42b, which were then converted to 43a and 43b by Buchwald reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The adverse effects of these drugs may be linked to the lack of specificity or selectivity. Tyk2 JH1 inhibitors such as 1 , 2 , 3 (PF-06700841), , and 4 (PF-06826647) (Figure ) have been reported, with 3 and 4 in clinical trial phases II and I, respectively. Like the JH1 inhibitors of other Jak family members, these inhibitors are only modestly selective as they also show significant activities against other Jak family members.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the initial SAR investigation showed that this platform could have a vertically flipped binding mode. Introduction of a 1‐methyl‐3‐pyrazolyl group at the 7‐position of 45 directed toward the solvent‐exposed region led to a significant improvement in TYK2‐inhibitory potency, and further modification resulted in the identification of 46 …”
Section: Exploitation Of Solvent‐exposed Regions For Structure‐based mentioning
confidence: 99%
“…These include highly lipophilic moieties such as (substituted) phenyls, aromatic amines, biaryl constructs and heterocyclic aromatics. Using these structures as scaffolds, a great number of studies have designed new smKIs by adding different side groups [ [117][118][119]. Combining scaffolds to create a new multi-kinase-targeting smKI is also a commonly used strategy [120].…”
Section: Essential Structuresmentioning
confidence: 99%